I need help with this 1st problem and if you can help me this one and with the other ones I will post them thx
I need help with this 1st problem and if you - 1

Answers

Answer 1
Answer: 10 people....

40            3                120
----     *   -----      =     --------   = 30
1              4                  4

Within 30, 1/3 got a part in the show....

30            1                   30
-----     *   ----         =    -------   = 10 
1               3                   3    

10 people got parts 



Related Questions

What is half of seven because I working on area and circumference
What is the equation for x=-3 and y=-7
A flower has ten pedals.During a storm,five of the pedals fall off.Write a decimal to show what part of the pedals is left
Derick studied 13 1/2 hours this week for a spelling bee. Write the number of hours as a decimal.
What did the scout say after fixing the little old lady's bicycle horn?

I know its a lot but i dont understand it i have tried to understand it

Answers

The method for this kind of thing is PEMDAS
1. Parentheses
2. Exponents
3. Multiply
4. Add
5. Subtract
Do it in this order.
Tell me if you need more help.

70-q-q-2q=80 We'll this is confusing

Answers

70 - q - q - 2q = 80

-4q = 80 - 70

-4q = -10
q = -10/-4

q = -2.5 
70-q-q-2q=80
or, 70 - 2q - 2q = 80
or, 70 - 4q = 80
or, -4q = 80 - 70
or, -4q = 10
or, q = 10/-4
or, q = -2.5   (ans)

in mathematics, central tendency is the tendency of data values to cluster around some central value. What does a measure of variability tell you about the central rendency of a set of data?

Answers

Measures of variability would describe how the central tendency is influenced by the data. Since the central tendency is the tendency of data values to cluster around some central value, then measures of variability would show how strong the central tendency is.

Answer:

what the other person said is correct

Step-by-step explanation:

Every day, Jason runs for 34 minutes and lifts weights for 44 minutes. How many minutes will Jason spend working out in 7 days?

Answers

34*7=238
44*7=308
238+308=546
You add 34 and 44 and you get 78. Then you multiply 78 by 7. You should get 546. So Jason will spend 546 minutes working out in 7 days

If the quadratic equation x^2 + 18x +74=0 is rewritten in the form (x-p)^2 = Q what is the value of Q?A) -155

B) -74

C) 7

D) 9

Answers

If the quadratic equation x^2 + 18x +74=0 is rewritten in the form (x-p)²= Q. Then the value of Q is 7.

What is a quadratic equation?

It is a polynomial that is equal to zero. Polynomial of variable power 2, 1, and 0 terms are there. Any equation having one term in which the power of the variable is a maximum of 2 then it is called a quadratic equation.

Given

The quadratic equation \rm x^(2) + 18 x + 74 = 0.

How to find the value of Q?

If the quadratic equation \rm x^(2) +18x +74=0 is rewritten in the form

\rm (x - p)^2 = Q

Add and subtract 9² in the equation.

\rm x^2 + 18x + 9^2 - 9^2 + 74 =0

We know the formula

\rm (a + b)^2 = a^2 + 2ab + b^2

Then equation will be

\begin{aligned} \rm (x + 9)^2 - 81 + 74 &= 0\n\ \ \ \rm (x + 9)^2 - 7 &= 0\end{aligned}

Add 7 both the sides, then

\rm (x + 9 )^2 = 7

Thus the value of Q is 7.

More about the quadraticequation link is given below.

brainly.com/question/2263981

The value of Q "option C) 7" is correct option.

Step-by-step explanation:

The given quadratic equation:

x^2 - 18x +74=0

To find, the value of Q = ?

x^2 - 18x +74=0

Adding both sides 81, we get

x^2 - 18x +81+74=81

x^2 - 2(x)8 + 9^2 = 81 - 74

Using the algebraic identity,

(a-b)^(2) =a^(2) +b^(2) -2ab

(x-9)^(2) =7 is the form of  (x-p)^2 = Q

Here, P = 9 and Q = 7

Thus, the value of Q "option C) 7" is correct option.

Given the functions below, what is f(x)−g(x) ?f(x)=7x3−10x2−5g(x)=2x3+7x2−9
A
5x3−17x2+4

B
5x3−3x2−14

C
9x3−3x2−14

D
5x3−17x2−14

Answers

Answer:

f(x)-g(x)=5x^3-17x^2+4 which appears as option A

Step-by-step explanation:

Simply subtract the function's expressions as shown below, and combine like terms to express the final result:

f(x)=7x^3-10x^2-5\ng(x)=2x^3+7x^2-9\nf(x)-g(x)=7x^3-10x^2-5-[2x^3+7x^2-9]\nf(x)-g(x)=7x^3-10x^2-5-2x^3-7x^2+9\nf(x)-g(x)=7x^3-2x^3-10x^2-7x^2-5+9\nf(x)-g(x)=5x^3-17x^2+4